UMS students awareness towards participation in co-curriculum activities / Nur Suraya Sukandar - Sukandar, Nur Suraya (2010)
Research has indicated that co-curriculum activities are important to students in the university. More specifically, studies have been conducted that there is an effect of co-curriculum activities towards development and character building of students. The purpose of this study is to determine the awareness towards participation of co-curriculum activities among UMS students. There are several objectives highlighted as guideline to the study. First is to study the level of awareness on participation in co-curriculum activities among students in UMS. Second is to determine the influence of students' knowledge of co-curriculum activities upon their attitude towards participation in co-curriculum activities. Third is to examine the differences awareness on co-curriculum activities among gender. 100 fulltime students from two schools in UMS have been selected as the respondents to answer the questionnaires that choose according to random sampling. Based on the analysis of the findings, most of the respondents are aware of their participation in co-curriculum activities. In conclusion, the participation in co-curriculum activities among students can benefit them in term of development of soft skill, character building and reshape their decision making.